Metal-Based Complexes as Pharmaceuticals for Molecular Imaging of the Liver - Julia Greiser; Wolfgang Weigand; Martin Freesmeyer (MDPI AG, 2019)
This article reviews the use of metal complexes as contrast agents (CA) and radiopharmaceuticals for the anatomical and functional imaging of the liver. The main focus was on two established imaging modalities: magnetic resonance imaging (MRI) and nuclear medicine, the latter including scintigraphy and positron emission tomography (PET). The review provides an overview on approved pharmaceuticals like Gd-based CA and 99mTc-based radiometal complexes, and also on novel agents such as 68Ga-based PET tracers. Metal complexes are presented by their imaging modality, with subsections focusing on their structure and mode of action. Uptake mechanisms, metabolism, and specificity are presented, in context with advantages and limitations of the diagnostic application and taking into account the respective imaging technique.